The step-up mindset for new managers - Margo, Manning (St Albans Panoma Press, 2016)
You need to be more than talking a good game, your wants and potential must be converted into tangible outcomes. New managers will not be given forever to prove themselves, and the prepared manager will be up and running quickly. Most managers have the same worries and confidence dips. This is the book that will cut through the unnecessary hype and methodologies to give you a highly effective yet simple approach to becoming a great manager. Stop the ifs and buts. Drop the "I am new to the job" excuses and focus your efforts on getting the job done, and done well. Own your reputation and start delivering confidently and knowledgably.
Keywords: BUSINESS & ECONOMICS / Motivational; Executive ability; Management; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS